RANCANG BANGUN APLIKASI POINT OF SALE TANAMAN HIAS BERBASIS WEB DI ANUGRAH HIJAU FLORIST & NURSERY - Reni Febriani; M Yusuf Romdoni; Muhammad Dwi Nugraha (LPPM Unbaja, 2023)
The development of information technology is currently growing very rapidly, the advancement of information technology has triggered large and small companies to use information technology as a tool to face and win the competition which is increasingly fierce and competitive. Anugrah Hijau Florist & Nursery is a business that is engaged in the sale of ornamental plants and provides various kinds of medicinal plant products, seeds, fertilizers, and plant care needs. The sales method used by Anugrah Hijau Florist & Nursery currently buyers come directly to the location. The management of the transaction process used today is still conventional, there is no digital media to accommodate product data or sales and purchase transactions, the slow processing of sales transactions, and relying on catalog books makes plant data out of sequence which results in decreased employee performance and delayed reporting. The problem that will be studied in this research is about the design of the Point of Sale application that can change the transaction process that is still manual or conventional into digitalization. By using the UML method, the SDLC Prototype model, making Point of Sale applications can communicate well between developers and customers, developers can work better in determining customer needs, customers play an active role in system development, implementation becomes easier because users know what they expect. This application also uses the Laravel Framework to improve the development process which is getting faster and saves more time. The results obtained from this study are that the sales transaction process is more effective and efficient, product data and sales and purchase transactions are stored properly, and the reporting process becomes easier.